Performance of the ATLAS track reconstruction algorithms in dense environments in LHC Run 2 - Aaboud, M; Aad, G; Abbott, B; Abdallah, J; Abdinov, O; Abeloos, B; Abidi, S H; AbouZeid, O S; Abraham, N L; Abramowicz, H; Abreu, H; Abreu, R; et al. (The European physical journal. C, Particles and fields, 2017)
With the increase in energy of the Large Hadron Collider to a centre-of-mass energy of 13 [Formula: see text] for Run 2, events with dense environments, such as in the cores of high-energy jets, became a focus for new physics searches as well as measurements of the Standard Model. These environments are characterized by charged-particle separations of the order of the tracking detectors sensor granularity. Basic track quantities are compared between 3.2 fb[Formula: see text] of data collected by the ATLAS experiment and simulation of proton-proton collisions producing high-transverse-momentum jets at a centre-of-mass energy of 13 [Formula: see text]. The impact of charged-particle separations and multiplicities on the track reconstruction performance is discussed. The track reconstruction efficiency in the cores of jets with transverse momenta between 200 and 1600 [Formula: see text] is quantified using a novel, data-driven, method. The method uses the energy loss, [Formula: see text], to identify pixel clusters originating from two charged particles. Of the charged particles creating these clusters, the measured fraction that fail to be reconstructed is [Formula: see text] and [Formula: see text] for jet transverse momenta of 200-400 [Formula: see text] and 1400-1600 [Formula: see text], respectively.